Effects of Partial Replacement of Soyabean Meal with Bread Fruit (Artocarpus altilis) Seed Meal in Broiler Finisher Diets on Their Performance, Water Consumption, Nitrogen Retention and Carcass Characteristics - Nwokoro, Smart O.; Obasuyi, Joseph O.I. (International Journal of Poultry Science, 2006)
The study was carried out to determine the effects of partial replacement of soyabean meal in broiler finisher chickens diets with breadfruit seed meal on their performances, nitrogen retention and carcass characteristics. 300, four weeks old broiler chickens were divided into 15 replicates of twenty birds each such that three replicates were allocated to a diet. The diet (2900kcalMEkg-1 and 20%CP were formulated such that 26.7% of soyabean meal in the control diet were partially replaced with breadfruit meal at 0, 10, 20, 30 and 40 percent (weight- for- weight). The birds were fed and watered ad libitum. Results emanating from the study indicated that final body weight, weight gain, feed intake, water intake, nitrogen retention, eviscerated carcass weights and head portion were significantly (P< 0.05) affected by dietary treatments. Apart from the nitrogen retention and head portion, the control diet (diet 1) recorded the highest values and there were significant (P< 0.05) decrease between diet 1 (0) and diet 5 (40%). The best feed per gain ratio, dressing percentage and nitrogen retention were recorded in diets 1 (0), 1(0) and 3(30) respectively. There were significant increases in nitrogen retention between diet 1 and 3, followed by significant decreasing order thereafter. Higher level of breadfruit seed meal replacement beyond 30% seems not to favour the broiler finisher chickens under the conditions of the study.